Keratitis caused by Pseudomonas aeruginosa: treatment in the experiment - Malachkova, Nataliia; Kryvetska, Nelia; Kryvetskyi, Volodymyr (ScienceRise: Medical Science, 2020)
The aim of the study was to investigate the effectiveness of treatment of keratitis caused by Pseudomonas aeruginosa using official ophthalmic forms of antibiotics, which are effective against the pathogen. Materials and methods. Adult 36 rabbits weighing 3–3.5 kg were undergone the causing of purulent keratitis by applying a clinical strain of P. aeruginosa as a suspension of one-day culture of the microorganism at a concentration of 5×108 CFU/ml on the partially de-epithelialized (approximately 1 cm2) cornea followed by coating for 24 hours with soft contact lens made of belafilcon A (water content: 36 %, oxygen permeability DK/t:110.0). In half of the cases, microbial biofilms were pre-grown on the contact lens surfaces via incubation into the broth culture of P. aeruginosa strain. The treatment of keratitis was performed with ocular official forms of antibiotics: levofloxacin 0.5 % (5 mg/ml), ciprofloxacin 0.3 % (3 mg/ml), tobramycin 0.3 % (3 mg/ml). Their effectiveness against the strain of P. aeruginosa was previously proven in vitro. The animals were divided into three corresponding as for severity of keratitis groups, in each of which treatment was performed with one of the three above antibiotics. In half of the cases within each group, the antibiotic was combined with the ocular official form of decamethoxine 0.02 % (0.2 mg/ml). The antibiotics were used in the mode of the most frequent instillation for the first 2 days after the onset of purulent keratitis, then 5 and 4 times a day. The assessment included evaluation of clinical signs, culturing, ophthalmological examination of the cornea with fluorescein test and photofixation. Animals were removed from the study on days 7th, 10th, 14th (depending on the term of epithelialization of the affected cornea). Results. Totally, 36 cases of purulent keratitis caused by P. aeruginosa in rabbits were modelled: 8 moderate (22.2 %), 13 semi-severe (36.6 %), 15 – severe (41.7 %). Regardless of the chosen antibiotic, 10-12 hours after removal of the infected contact lens and the start of treatment, there was mostly a burst enhancement of the inflammatory process. Subsequently, the inflammatory signs showed a gradual attenuation with complete corneal epithelialization for 7th–8th days (for moderate keratitis), 10th–12th days (for severe and semi-severe in Group I and Group III) and (12th–14th days for severe and semi-severe in Group II). In comparison with the Group I (levofloxacin 0.5 %), the reducing of the corneal inflammation and lesion epithelialization within the Group II (ciprofloxacin 0.3 %), was 1–2 days delayed. The use of 0.3 % tobramycin (Group III) provided the highest control of purulent inflammation during the first three to four days, but further there was a slowdown in the positive dynamics and delayed epithelialization compared with Group I. For all study groups, the use of combination antibiotic therapy with decamethoxine was accompanied by acceleration in regression of purulent-inflammatory lesions, especially due to a decrease in conjunctival response and pyorrhea. Among the outcomes, in most of cases (69.5 %) there were areas of corneal opaque turbidity of various sizes. Total leucoma was noted in more than a third of cases; always due to severe keratitis. It was managed to avoid the complications that could lead to eye loss (corneal abscess, perforation, malacia) in all animals. The culturing from the surface of the eye has shown a decrease from 100 % to 63.9 % in presence P. aeruginosa after 48 hours and the whole pathogen disappearance after 3 days of treatment. However, in 11 of 15 severe keratitis (30.6 % of total observations) microbiological tests of the cornea, obtained after removal of animals, were positive as for P. aeruginosa even after complete lesion epithelialization. Conclusions. Treatment of experimental keratitis caused by P. aeruginosa, with antibiotics, to which the sensitivity of pathogen is proven, in the mode of the earliest and most frequent instillations on the first 48 hours in combination with removal of purulent masses provides reducing of inflammation, restoring of cornea surface and prevents the most serious complications, e.g. corneal perforations and keratomalacia. Early and active antimicrobial treatment with effective drugs led to the elimination of P. aerugenosa from the ocular surface in the first 2–3 days. However, in 30.6 % of cases there was no complete eradication of the pathogen from the cornea. The choice of antibiotic from those, to which the sensitivity of P. aerugenosa is proven, did not have a significant influence on treatment outcome. Concomitant use of decamethoxine makes better effect and somewhat improves the results